PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA SMA EFATA SOE - Raymond Maulany; Nyongki Bako (TeIKa, 2020)
The role of information technology has become a human need at this time. Library information system is a very important thing in the world of education because the library is a window to the world. Efata Soe High School wants to have a Web Based Library Application. The use of this technology will function as an integrated system, to provide information and support management decision making in a library. This web-based library application system utilizes computer hardware and software, as well as manual management model procedures and database decision making. The use of platforms makes it easy to access the system anywhere by using devices connected to the network. But in this design the new system used is in the local school network, not yet connected to the internet network. With this system, it really helps the Efata Soe High School library in managing book collections.